Increasing the Effective and Efficient Harvest of Rice (Oryza sativa. L) in Nabire Barat District - Simon Matakena; Syusantie Sylfia Sairdama; Marloza Roy; Julianus Inggesi (Postgraduate, University of Mataram, 2025)
Increasing the effectiveness and efficiency of rice harvesting (Oryza sativa. l) in west nabire district, nabire regency, aims to determine the effectiveness and efficiency of the use of Combine Harvester in rice harvesting in West Nabire District, Nabire Regency. This study used a survey method with a sample of 26 respondents by simple random sampling, with an interview method using a previously prepared questionnaire. The results of the study showed that the use of the Combine harvester harvesting machine was more effective than the manual rice harvesting process with an effective value of 1.073, with a cost reduction of Rp 747.385.4 and a reduction in grain loss during harvest of 586.44 kg. The use of Combine harvester has a beneficial impact because it can reduce production by Rp 747.385.4 and reduce crop loss by 586.44 kg of grain.